How did we get to the deficit spectrum of the economic crisis? - Alexandru Bodislav (Romanian Journal of Fiscal Policy (RJFP), 2012)
The economies of developed countries of the 21st century benefit from the unseen-till-now prosperity; life standard that suffered a hard landing starting with 2007 and that seems to evolve in a chain-saw model for the crisis development. The forecast is based on the first in, last out principle; first in the US, last out the emergent countries that are under the contagion process and under inefficient governance and which started as a subprime crisis and continues as a deficit crisis. These nations produced one of the highest life standards in history. How was this possible? It is believed that the origin of this prosperity (before and after the crisis) is in the development of an economic system that embraces the free enterprise, capitalism and competition because prosperity represents is the crossroad between the self interests of many. This research paper tries to underline the factors that led to the actual development of the crisis; from the bankruptcy of Lehman Brothers to the unstable and not well directed actions of governments around the world and to these first tier layers there are added the second tier layers that include the political vantage point that influences the paths that are followed for limiting the negative aspects of the economic crisis and to improve new opportunities that appear as a result of openness and collaboration. The muddling through principle was adopted by the Obama Administration and this fact is one of the main factors that ease the deployment of near future economic improvement for the United States, but for the long run this isn't a solution to develop a healthy economy and create sustainable economic growth.
Keywords: E32; E63; O16; O47; P12; 330; capitalism; deficit crisis; economic crisis; global synchronism; PIIGSB